Kemampuan Literasi Matematika Siswa SMA dalam Mengerjakan Soal PISA Ditinjau dari Gaya Kognitif - Nurul Qomariyah; Sumartono Sumartono; Lusiana Prastiwi (JIMAT: Jurnal Ilmiah Matematika, 2025)
This research aims to describe the mathematical literacy ability of high school students in solving PISA problems reviewed from the cognitive style of field Dependent (FD) and Field Independent (FI). The research uses a descriptive qualitative approach with four class X students as subjects, which is determined based on the GEFT test results. Data collection was carried out through a math literacy ability test based on six levels of PISA and interviews to explore the student's thinking process. The research results show that students with FI cognitive style are able to meet level 1 to 5 math literacy indicators, while FD students can only meet level 1 and 3 indicators. Both types of cognitive forces are unable to reach the level 6 indicator. This study concluded that cognitive style affects students' mathematical literacy ability, especially in understanding information, building mathematical models, and drawing conclusions.